Hearing Loss in Mucopolysaccharidosis - Bicalho,Cibele Gomes (2021)
Abstract Introduction Mucopolysaccharidosis (MPS) is a set of rare diseases caused by deficiency of lysosomal enzymes that lead to the accumulation of glycosaminoglycans (GAG) in tissues and organs, which, in turn, is responsible for the multisystemic clinical, chronic, and progressive symptoms. Objective To describe the profile of the otorhinolaryngological clinical examination and audiology tests of patients with MPS disease. Methods The present study is a case series. The evaluation was performed, initially, in 24 patients with MPS types I, II, IIIA, IV and VI. Results The most common hearing complaint was hearing loss, which was confirmed by audiology tests in almost 100% of the patients, most of whom presented conductive hearing loss. Conclusions It is important to evaluate the complaints, physical examination, and audiology tests in patients with MPS. The otorhinolaryngologistshould be part of the group of professionals that follows these patients to better monitor their hearing and provide early hearing rehabilitation.